Studi Perubahan Sosial Komunitas Masjid Jogokariyan Yogyakarta : Tinjauan Sosiologi-Sejarah - Arrozy, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2020)
This study observed social change a community of mosque in Kampung Jogokariyan special region of Yogyakarta. With the management capabilities and the leadership who respect to their figures when pioneered since 1960 maked a significant of social change. This study use a historical-sociology approach with Max Weberâ€™s classic theory framework. From this research indicate the revival of religious solidarity factor has encouraged the movement political-economy. This subject is a characteristic of the collective on contemporary IslamicÂ Â movement in urban Java.